Dewetting of liquid film via vapour-mediated Marangoni effect. (7th June 2019) - Kim, Seungho; Kim, Joonoh; Kim, Ho-Young
Abstract : Liquid films on wettable solid surfaces can be disturbed to dewet when low surface tension liquids or surfactants are added because the surface tension difference gives rise to stresses on the film interface. Here we consider an alcohol drop placed above a thin aqueous film, which punctures a hole in the film starting from underneath the alcohol drop. Such film dewetting is attributed to the Marangoni effects caused by the spatial gradient of alcohol vapour concentration. We measure the liquid–gas interfacial tension of aqueous liquids rapidly responding to the surrounding isopropyl alcohol vapour concentration, and observe evolution of the film morphology consisting of central hole, fringe film, thinning region and bulk. We construct scaling laws to predict the dewetting rates of the film by considering the Marangoni stress, viscous shear stress and evaporation. It is shown that our experiments are consistent with our theory.